A Skills beyond School Review of Germany - Fazekas, Mihály [Verfasser]; Field, Simon [Verfasser] (OECD Publications, 2013)
"This review is one of a series of country reports on postsecondary vocational education and training (VET) in OECD countries. Two main sub-sectors were examined in this review of Germany. First, there are advanced vocational examinations regulated by the federal Vocational Training Act (Fortbildungsgänge nach dem Berufsbildungsgesetz) and in some cases also by the individual chamber regulations of the chambers of crafts and trades and of the chambers of industry and commerce (Fortbildungsgänge nach Ordnung der Handwerks- und Industrie- und Handelskammern). Second, there are trade and technical schools (Fachschulen) regulated under Land law. This review follows a standard methodology. Germany initially prepared a country background report (Hippach-Schneider, U., et al., 2012). An OECD team then visited Germany on 26-30 March and 18-22 June 2012 where they discussed the issues arising with a wide range of stakeholders." The structure of this report is as follows: "The first chapter places the review of Germany in the context of the OECD policy study of postsecondary VET, presents the structure of the report, describes the main features of postsecondary VET system in Germany, compares its main features with other systems internationally, explores some key international indicators bearing on the system and examines its strengths and challenges." The following chapters advance policy recommendations, referring to: "Transition to academic higher education" (chapter 2); "Better information on preparatory courses for examinations" (chapter 3); "Quality of examinations" (chapter 4); "Teachers and trainers in Fachschulen" (chapter 5); "Workplace training at Fachschulen" (chapter 6); "Fachschule provision and the labour market" (chapter 7). (Textauszug, BIBB-Doku)
Keywords: I 1.5 Internationale Organisationen & Institutionen; S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; S System beruflicher Bildung; I 2.1 Deutschland; OECD; Bildungspolitik; Berufsbildung; Hochschulzugang; Fortbildung; Bildungspersonal; Lernen am Arbeitsplatz; Schulische Berufsausbildung; Fachschule; Bildungsangebot; Arbeitsmarkt; Bundesrepublik Deutschland